Professor de inglês: um olhar sobre a atuação docente e profissional - Beligoli, Cláudia de Lima (2015)
This study was developed with the goal of discussing the challenges of teachers formation and professional training of students-teachers from the Specialization in English Language course, already working as teachers, in a private institution located in the ABC region, in São Bernardo do Campo. In order to do so, it discusses the difficulties faced by these teachers in either private or public regular schools, in language courses, as well as in private teaching, aiming to reflect on their professional and academic practice. Some authors who have reflected upon this theme were referred to, such as Maria Antonieta Alba Celani, Antonio Nóvoa, Maurice Tardif, Francisco Imbernón, among others. The first phase was accomplished through a questionnaire with open questions and fourteen participants. After analysing the answers, a new questionnaire was applied aiming to deepen the aspects initially observed. The data from this study were analysed through the references of content analysis from Laurence Bardin and Maria Laura Puglisi Barbosa Franco. Such teachers looked for the Specialization Course in English Language due to the need for more theoretical foundation in the area. Results have shown that the majority of student-teachers started their teaching career as ex-students in the language schools where they had studied. The ones surveyed reported that the major challenges and difficulties of the occupation include dealing with different didactic materials, public, age and methodologies, beyond the lack of student interest, employment instability, minimal recognition of the profession and the low income. In their reports, after the Specialization course completion, it was possible to observe that all students significantly considered the importance of the course. Although they do not feel satisfied with the current scenario, almost all the teachers want to follow the teaching career and proceed in the studies of the English Language.